Estudio del bosón de higgs H02 en el modelo 3-3-1 - Gil Ramírez, Ricardo Jaime (2018)
In this work we study the production of the Higgs H0 in p-p machines through the Drell- Yan mechanism and gluon-gluon fusion,Assuming extension 3-3-1 containing the heavy leptons.We will show that to identify this bos´on we will use the respective reasons for decay.The cross sections are given to the LHC (Large Hadron Colider) with energy of √s = 14 TeV. Events and significances are discussed for two possible values of integrated luminosity of 300 fb−1 y 3000 fb−1.